Melanoma Genomics - Julia Newton-Bishop; D. Timothy Bishop; Mark Harland (Medical Journals Sweden, 2020)
The incidence of cutaneous melanoma continues to increase in pale skinned peoples in Europe and elsewhere. Epidemiological studies identified genetically determined phenotypes such as pale skin, freckles and red hair, and sunburn as risk factors for this cancer. The development of many melanocytic naevi is also genetically determined and a strong melanoma risk phenotype. Not surprisingly then, genome wide association studies have identified pigmentation genes as common risk genes, and to a lesser extent, genes associated with melanocytic naevi. More unexpectedly, genes associated with telomere length have also been identified as risk genes. Higher risk susceptibility genes have been identified, particularly CDKN2A as the most common cause, and very rarely genes such as CDK4, POT1, TERT and other genes in coding for proteins in the shelterin complex are found to be mutated. Familial melanoma genes are associated with an increased number of melanocytic naevi but not invariably and the atypical naevus phenotype is therefore an imperfect marker of gene carrier status. At a somatic level, the most common driver mutation is BRAF, second most common NRAS, third NF1 and increasing numbers of additional rarer mutations are being identified such as in TP53. It is of note that the BRAF and NRAS mutations are not C>T accepted as characteristic of ultraviolet light induced mutations.